The distribution and habitat preferences of wild ungulates and cattle in Lochinvar National Park, Zambia and the use of resources by people living adjacent to the park - Lumbwe, Fainess Chaona (FitzPatrick Institute of African Ornithology, 2023)
(1) The distribution and habitat preferences of wild ungulates and cattle were determined from observations and counts in Lochinvar National Park and the Game Management Area (GMA) on the west em part of the park on the Kafue river floodplain of Zambia over five months. Oribi, zebra and lechwe were the most widely distributed wild ungulates using habitat patches inside and outside the park. Although the distribution of buffalo was restricted within the park, the species was found in all the habitat types unlike lechwe and zebra that preferred only the floodplain and termitaria areas. Wildebeest preferred the termitaria and floodplain areas inside the park. The highest lechwe density was in Chunga floodplain with a density of 504.2/km2 followed by Mulindi GMA with 451.9/km2. The lowest lechwe density was in Mulindl termitaria with 0.4/km2. Zebra density was highest in Nampongwe floodplain with 118/km2 while the highest wildebeest density was on Gwisho dambo with 27/km2. Nampongwe floodplain had the highest oribi density with 2.8/km2. There were significant differences in the density of lechwe inside and outside the park in Mulindi. Zebra and oribi densities inside and outside the park in Mulindi were low and no differences could be noted. (2) The biomass production in the different habitats was determined by harvesting the above ground biomass in selected areas in each habitat. The termitaria were the most productive of the three habitat types with an estimated production of 4320kg/ha followed by the woodland with 3200kg/ha and the least production was in the floodplain with 2850kg/ha. Of this total, grasses made up 87.4%, 83. 7% and 72.5% of the production in the floodplain, termitaria and woodland respectively. There were no significant differences in biomass production between different habitat types, however, there were significant differences in biomass production within the same habitat. (3) The species composition of the dominant plants was different in all habitat types. and as a result, the forage availability in the different habitats also differed. The floodplain was dominated by Echinoehloa spp, Panicum repens and Oryza longistaminata whereas the termitaria was dominated by Hyparrhenia rufa, Setaria spp and Echinochloa colonum. The woodland was dominated by Setaria and Digitaria spp. (4) Cover was determined in the different habitat types using the Parker Step Point method. The highest amount of grass cover was in the floodplain with 46.6% followed by termitaria with 45.6% and the woodland with 13.3%. Non grass cover was highest in the termitaria with 15.8°, followed by floodplain with 9.4% and woodland with 0.5%. The woodland had the highest amount of litter with 66.5% followed by the floodplain with 30.7%. The termitaria had the least amount of litter with 24.9%. The highest amount of bare ground was in the woodland with 19.8% followed by termitaria with 13.8% and the floodplain with 13.3%. There were significant differences in the proportion of grass and non-grass cover in all habitat types. There were no significant differences in the proportion of litter and bare ground between the floodplain and tennitaria and between floodplain and woodland however, there were significant differences in the proportion of litter and bare ground between the tennitaria and woodland. (5) A questionnaire survey revealed that game meat and grazing land are the two main resources that are used by people near the park. The main problems faced by people living near the park is destruction of crops by problem animals like baboons and bushpigs and the transmission of diseases like tuberculosis from game to livestock. The survey also revealed that people are forced to travel inside the park because it is the shortest route to various destinations. Others travel inside the park because the main sources of employment in the area are found inside the park. Game seems to be used to the presence of people and will only run away when closely approached or when people are travelling using a vehicle. (6) The results of the study do not support the hypothesis that cattle can be accommodated in Lochinvar National Park with no adverse effect on lechwe and other large herbivores. Cattle and game use the same areas outside the park in Mulindi but the areas are used at different times in the year. (7) Lochinvar National Park needs a clear burning policy to effectively manage the bush encroachment problem and overgrazing in some areas inside the park. The income generated by the park should be ploughed back into the management of the park in order to effectively control poaching, human encroachment into the park and to monitor the activities and movements of people inside the park.